Work-in-progress: Multi-stakeholder dialogue for policy recommendations on algorithmic fairness - Webb, H; Koene, A; Patel, M; Vallejos, E (Association for Computing Machinery, 2018)
The multi-stakeholder approach is a valuable methodology for governance and policy development. In this paper we describe our use of the approach in the ongoing UnBias study, which seeks to identify opportunities for the effective governance of algorithmic online services. We use the multi-stakeholder methodology to bring together experts from relevant sectors including academia, education, government, regulation, law, civil society, media, and industry and commerce. This paper outlines how our work so far has facilitated open and constructive debate that can drive the development of meaningful policy recommendations. We also describe some challenges of this approach and our next steps towards producing actionable design and policy recommendations, including engagement with international industry standards development.1